Beyond Beta-Delta: The Emerging Economics of Personal Plans - Beshears, John; Milkman, Katherine L.; Schwartzstein, Joshua (American Economic Review, 2016)
People make personal plans regarding whether, when, where, and how to undertake certain actions. We discuss three questions related to personal plans. First, what are the effects of plans on behavior? Second, when are plans formed? Third, how do plans deviate from optimality? For each of these questions, we (a) offer a brief overview of research that sheds light on the issue and (b) identify gaps in current knowledge. We emphasize connections to the growing theoretical literature that gives personal plans a substantive role, but we conclude that more research is needed, especially on the latter two questions we cover.